NCED expression is related to increased ABA biosynthesis and stomatal closure under aluminum stress - Gavassi, Marina Alves [UNESP]; Silva, Giselle Schwab [UNESP]; da Silva, Carolina de Marchi Santiago; Thompson, Andrew J.; Macleod, Kyle; Oliveira, Paulo Marcelo Rayner; Cavalheiro, Mariana Feitosa; Domingues, Douglas Silva [UNESP]; Habermann, Gustavo [UNESP] (Elsevier, 2021)
Aluminum (Al)-induced decrease in leaf hydration has been associated with low gas exchange, especially stomatal conductance (gs). However, the mechanisms explaining these responses are unclear. Citrus limonia was exposed to 0 and 1480 μM Al in nutrient solution for 90 days to test whether the low gs and leaf hydration in plants exposed to Al is associated with increased 9-cis-epoxycarotenoid dioxygenase (NCED) gene expression and abscisic acid (ABA) biosynthesis. Relative leaf water content (RWC), water potential (Ψw) and gas exchange in the leaves, as well as leaf and root ClNCED3, ClNCED1 and ClNCED5 expression and accumulation of ABA and its metabolites (phaseic acid, dihydrophaseic acid, (+)-7′-hydroxy-ABA and ABA-β-D-glucosyl ester) were measured. Aluminum up-regulated ClNCED3 and induced ABA accumulation in the roots before impairments in leaf water status (low Ψw, RWC and gs) could be observed. Leaf ABA concentration increased from 7 to 90 days and this could be partially explained by the up-regulation of ClNCED3, ClNCED1 and ClNCED5 in this organ. Stomatal closure occurred concomitantly with the increase of ABA concentration, and this result provides further evidence of the role of ABA modulation of plant hydration under Al stress.
Keywords: ABA; Aluminum; Citrus; NCED genes; Plant signalling; Water relations